Pelatihan Sanitasi Inklusi Mewujudkan Akses Sanitasi Layak bagi Penyandang Diasbilitas di Kelurahan Babau Kabupaten Kupang: Inclusive Sanitation Training to Achieve Access to Proper Sanitation for People with Disabilities in Babau Village, Kupang Regency - Karolus Ngambut; Debora Gaudensiana Suluh; Ety Rahmawaty; Siprianus Singga (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Access to proper sanitation for all people is one of human rights. Even though access to latrines in the community continues to increase, there are still vulnerable groups such as women, children and people with physical disabilities who are still limited in getting their rights. Community service activities aim to increase public knowledge about inclusive sanitation, namely sanitation that can be reached by persons with disabilities. The method of activity carried out is training and making latrines with examples of inclusive sanitation. The targets of the training activities are community level stakeholders and persons with disabilities. The results of the activity showed an increase in respondents' knowledge about inclusive sanitation. Apart from that, model building can increase access to sanitation for persons with disabilities. The construction of model latrines involves relevant stakeholders. It was concluded that inclusive sanitation training methods and development of inclusive sanitation models can increase access to proper sanitation for persons with disabilities.